(untitled) (Research, Society and Development, 2022)
We evaluated the working number steps (STEPS) of 25 military police officers (MPOs: day shift n = 14 and night shift n = 11) from the Military Police of São Paulo State (PMESP) while patrolling São Paulo city center and its association with metabolic syndrome (MetS) indicators. The participants’ body composition and anthropometric parameters: body mass index (BMI), fat-free mass (FFM), skeletal muscle mass (SMM) and clinical and laboratory data: systolic (SBP) and diastolic (DBP) blood pressure, and fasting plasma levels of glucose, glycated hemoglobin A1c (HbA1c), insulin, HDL-cholesterol, triacylglycerol (TG), and C-reactive protein (CRP) were also measured. According to the number of steps taken during the daily 12 h working period, the MPOs were divided into three groups: 600-2,000, 2,001-8,000, and >8,000 steps. On average, each participant took 5169 ± 614 steps per 12 h shift. While MPOs from the night shift walked 25% more than the day shift (6188±1069 vs. 4367±664), this difference was not statistically significant. Notably, the BMI, FFM (13.4%), SMM (14.5%), plasma HDL-cholesterol levels (32.2%), and DBP (19.1%) were significantly higher in group 1 compared to the other two groups. Furthermore, reduced physical activity, age, BMI, and tenure at PMESP were associated with increased MetS indicators. Overall, MPOs performing less than 2,000 steps per shift presented marked changes in body composition and plasma measurements and a higher MetS prevalence (64%) than those who were more physically active.